PENGARUH LEVERAGE, GOOD CORPORATE GOVERNANCE, KULAITAS AUDIT TERHADAP MANAJEMEN LABA: Studi Empiris Pada Perusahaan Industrial Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2022 - Diana Nurul Wahyuni; Syamsuri, Syamsuri (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
This research aims to examine the influence of leverage, good corporate governance, audit quality on earnings management. This research uses a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The data analysis method used in this research is panel data regression using the Eviews version 10 application and Microsoft Excel. The population used in this research is industrial companies listed on the Indonesian Stock Exchange for the 2017-2022 period. The data collection technique in this research is a purposive sampling technique with the results of 55 populations becoming 11 research sample companies processed in this research. The research results simultaneously show that leverage, Good Corporate Governance, and audit quality simultaneously influence earnings management. Partially, leverage, institutional ownership and audit quality have no effect on earnings management, while independent commissioners have an effect on earnings management.